A misoginia medieval como resíduo na literatura de cordel - Assis, Anne Caroline Moraes de (2010)
The inferiority´s idea of women has been widespread in eastern and western civilizations. This design reached its apex in the Middle Ages, especially during the thirteenth and fourteenth centuries, when the Catholic Church severally controlled the social and religious life of Christians - especially women - backed by the religious tenets trough the Inquisition. That mentality misogynist supporters and gained strength and continued by subsequent centuries, being in the residual pulp fiction and contemporary perceptible through the experience, vocabulary and expressions used by cordelistas to describe and portray women. The popular character of literary discourse also denotes a relationship of power veiled in which the woman is labeled as inferior and sinful. Crystallized over the centuries, this thought came to the events taking place in contemporary literature. The Brazil´s northeast is largely patriarchal and sexist in its cultural roots, which are observed in the production of popular literature in verse, when the cordelistas construct their narratives from the social, cultural and religious, which back, usually at the thought of the Middle Ages. The aim of this work was to identify, from the reading and analysis of cordage, misogynist morality and the construction of the female characters such as waste mentality inherited from the Middle Ages, found in popular narratives. Therefore, the Teoria da Residualidade, and its related concepts, namely: Residual, Cristalização, Mentalidade and Hibridação Cultural is the basis of this analysis. After analyzing the cordéis, it was clear that the terms and expressions, as well as religious morality, referring to the feminine reinforce and confirm the thinking of medieval clerics that the origin of evil lies with the woman, in essence. In this context, the line appears as an instrument for maintaining social order and the preservation of morals and morality, according to the Christian mentality.